2020
DOI: 10.1097/mpg.0000000000002721
|View full text |Cite
|
Sign up to set email alerts
|

The Knowledge and Attitudes of Pediatricians in Israel Towards Vegetarianism

Abstract: Objectives: Pediatricians have an important role in the dietary education of children, and in the nutritional health of their patients. We aimed to assess nutritional knowledge, familiarity with guidelines, and attitudes of pediatricians regarding vegetarian diets. Methods: A cross-sectional study using a previously implemented questionnaire, distributed amongst a convenience sample of pediatricians in Israel. For each participant, scores of knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
3
9
0
1
Order By: Relevance
“…This result is supported by findings reported in similar studies conducted in other health professionals. 10,25 Affirms the findings found in previous research in which vegetarian participants demonstrated a higher level of nutritional knowledge than nonvegetarians about vegetarianism. 35-37 The possible justification for this could be, the fact of vegetarian diets are significantly related to adequate knowledge of the health benefits of vegetarian diets.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This result is supported by findings reported in similar studies conducted in other health professionals. 10,25 Affirms the findings found in previous research in which vegetarian participants demonstrated a higher level of nutritional knowledge than nonvegetarians about vegetarianism. 35-37 The possible justification for this could be, the fact of vegetarian diets are significantly related to adequate knowledge of the health benefits of vegetarian diets.…”
Section: Discussionsupporting
confidence: 87%
“…This finding is consistent with the results of similar studies. 24,25 In Peru, registered dietitians are predominantly women and represent 94% of professionals. 26 The proportion of women who attend human nutrition schools has always exceeded that of men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Europe [299][300][301][302], in the United States' medical schools [303][304][305] and elsewhere [306][307][308], an important lack of education about (clinical) nutrition in general is observed. Ironically, we often hear that "nutrition has little or even no impact on health and chronic diseases" [309].…”
Section: Lack Of Education In the Vegan Field Of Nutrition By Physicians And Dietitiansmentioning
confidence: 99%
“…Al respecto, esta investigadora, concluyó que los profesionales de la salud necesitan capacitación en el tema de vegetarianismo porque carecen de información sobre cómo lograr una dieta idónea. Hamiel 34 reportó un puntaje general de conocimiento promedio de una cohorte de pediatras encuestados de 37,9±16,0% en referencia a die-tas vegetarianas, destacando que solo el 13,4% consideraron que sus estudios los prepararon para atender a este tipo de población y las puntuaciones de conocimiento se correlacionaron positivamente con la actitud favorable en referencia a este tipo de dietas.…”
Section: íTem Evaluadounclassified